The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1017/jns.2014.51
|View full text |Cite
|
Sign up to set email alerts
|

Skipping breakfast leads to weight loss but also elevated cholesterol compared with consuming daily breakfasts of oat porridge or frosted cornflakes in overweight individuals: a randomised controlled trial

Abstract: Eating breakfast may reduce appetite, body weight and CVD risk factors, but the breakfast type that produces the greatest health benefits remains unclear. We compared the effects of consuming a high-fibre breakfast, a non-fibre breakfast, or no-breakfast control on body weight, CVD risk factors and appetite. A total of thirty-six overweight participants (eighteen men and eighteen women) (mean age 33·9 (sd 7·5) years, mean BMI 32·8 (sd 4·7) kg/m2) were randomly assigned to consume oat porridge (n = 12), frosted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 26 publications
2
69
0
Order By: Relevance
“…There is growing evidence to suggest that oat β-glucan increases satiety (Beck, et al 2009; Geliebter, et al 2015; Geliebter, et al 2014; Juvonen, et al 2009; Lyly, et al 2010; Pentikainen, et al 2014; Rebello, et al 2014; Rebello, et al 2013) and reduces post-prandial glycemia (Tosh 2013). The most likely mechanism is the viscosity generated in the gastrointestinal tract which has physiologic responses such as delayed gastric emptying, increased stomach distension, delayed intestinal transit, and reduced absorption of nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is growing evidence to suggest that oat β-glucan increases satiety (Beck, et al 2009; Geliebter, et al 2015; Geliebter, et al 2014; Juvonen, et al 2009; Lyly, et al 2010; Pentikainen, et al 2014; Rebello, et al 2014; Rebello, et al 2013) and reduces post-prandial glycemia (Tosh 2013). The most likely mechanism is the viscosity generated in the gastrointestinal tract which has physiologic responses such as delayed gastric emptying, increased stomach distension, delayed intestinal transit, and reduced absorption of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely mechanism is the viscosity generated in the gastrointestinal tract which has physiologic responses such as delayed gastric emptying, increased stomach distension, delayed intestinal transit, and reduced absorption of nutrients. These physiologic events stimulate satiation and satiety signals (Beck, et al 2009; Geliebter, et al 2015; Geliebter, et al 2014; Juvonen, et al 2009; Lyly, et al 2010; Pentikainen, et al 2014; Rebello, et al 2014; Rebello, et al 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that breakfast confers positive effects on body weight via appetite control (85). However, it is not clear whether the association of breakfast with healthier body weight is mediated by appetite control or other lifestyle factors also associated with breakfast consumption, such as increased physical activity (8688).…”
Section: Breakfast and Appetitementioning
confidence: 99%
“…Whilst observational studies are useful for establishing a potential link between a behavior and an outcome, randomized controlled trials are essential in order to make definitive causal statements. More recent studies using free-living designs over periods of weeks and months [5][6][7][8], combined with evidence from more tightly-controlled laboratory studies conducted within a single day [9][10][11] are beginning to address the causality of breakfast consumption, body weight regulation and health, whilst providing mechanistic insight into any causal effects.…”
mentioning
confidence: 99%